Perkembangan Sejarah Kota Jakarta Pasca Kemerdekaan Indonesia - Firmanda Dwi Septiawan (HEURISTIK: Jurnal Pendidikan Sejarah, 2022)
The city can be called a unit that legitimately stands alone and should be a separate field of study as well. The city center in Java after independence in 1945 sort of no guide in determining a city center. Most cities in Java until the 1970s, did not experience any significant expansion, although more and more new buildings were established. Most of the 'city center' regencies located around the square in Java still maintain their existence. Only the office of the Resident or Assistant Resident was abolished because it smelled colonial and did not comply with the new system of government.